2017
DOI: 10.1161/jaha.116.005058
|View full text |Cite
|
Sign up to set email alerts
|

Description of Abnormal Breathing Is Associated With Improved Outcomes and Delayed Telephone Cardiopulmonary Resuscitation Instructions

Abstract: BackgroundEmergency 9‐1‐1 callers use a wide range of terms to describe abnormal breathing in persons with out‐of‐hospital cardiac arrest (OHCA). These breathing descriptors can obstruct the telephone cardiopulmonary resuscitation (CPR) process.Methods and ResultsWe conducted an observational study of emergency call audio recordings linked to confirmed OHCAs in a statewide Utstein‐style database. Breathing descriptors fell into 1 of 8 groups (eg, gasping, snoring). We divided the study population into groups w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…Negative likelihood ratio = the likelihood of a patient with confirmed cardiac arrest to be labeled negative compared with a person without cardiac arrest (the smaller the likelihood ratio, the better the test to rule out cardiac arrest). * 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 . †Patients strictly with confirmed OHCA.…”
Section: Early Access and Cardiac Arrest Prevention Including Emergementioning
confidence: 99%
“…Negative likelihood ratio = the likelihood of a patient with confirmed cardiac arrest to be labeled negative compared with a person without cardiac arrest (the smaller the likelihood ratio, the better the test to rule out cardiac arrest). * 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 . †Patients strictly with confirmed OHCA.…”
Section: Early Access and Cardiac Arrest Prevention Including Emergementioning
confidence: 99%
“…Callers also describe this form of abnormal breathing as: gasping, snoring, or moaning. 15 , 28 Descriptors for agonal respirations often vary depending on the culture or language. Each local agency should investigate how lay people in the community are likely to describe agonal respiration and try to improve CA identification based on these results.…”
Section: Agonal Respirationmentioning
confidence: 99%
“… 12 , 45 , 71 , 72 Studies reported that time from call receipt to dispatch CA identification and start of CPR instruction is approximately 60 and 150 seconds. 28 , 32 , 45 The time from the bystander initiating the call to the first chest compression also varies widely. It is reported to be 180 seconds to over 5 minutes.…”
Section: Tcpr Process Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Gasping or agonal breathing is not “normal breathing” but rather an abrupt, often forceful inspiration and occurs only a few times per minute. Laypersons can mistake this primitive respiratory reflex as “snoring, snorting, moaning, or difficulty in breathing”, and not realize that the patient has suffered a cardiac arrest [7-10].…”
Section: Early Recognition Of Cardiac Arrestmentioning
confidence: 99%